Analysis of Basic Legal Considerations of Judges Against Perpetrators of Vanishing Campaign Props in Tanggamus Regency (Decision Study Number 91 / Pid.Sus / 2018 / PN Kot) - Annisa Amanda Pratiwi (IHSA Institute, 2019)
The next general election (election) is a form of democratic life that is the right of every citizen of the Republic of Indonesia. The problem in this study is how is the legal basis of judges judging the perpetrators of Campaign Props in Tanggamus Regency based on Decision Number 91 / Pid.Sus / 2018 / PN Kot and whether the judge's decision against the perpetrators of Campaign Props in Tanggamus Regency is based on Decision Number 91 / Pid.Sus / 2018 / PN Kot has fulfilled a sense of substantive justice? .Approach to the problem is carried out in an empirical juridical way by conducting research directly at the research location by looking, asking questions and hearing from the parties concerned. Data sources obtained by using primary data and secondary data. The procedure of data collection is done by means of library research and field research. Data analysis in this study used qualitative analysis. The results of the research and discussion show that the basis of Judge Considerations in Case Number 91 / Pid.Sus / 2018 / PN Kot defendants have legally and convincingly committed criminal acts and eliminated campaign props and were sentenced to prison for 1 (one) month each. . The judge does not impose a maximum sentence of more than 1 month and 15 days. The suitability of the Judge's decision to impose a criminal offense against the campaign props with the applicable legal provisions. which is lighter than the claim by the Public Prosecutor, which is six months in prison and has fulfilled the elements in the Article. Suggestion, the judge must consider the element or purpose of eliminating the campaign props.